The strange case of Origami Yoda - Angleberger, Tom (Angleberger, Tom. Origami Yoda book., 2010)
Sixth-grader Tommy and his friends describe their interactions with a paper finger puppet of Yoda, worn by their weird classmate Dwight, as they try to figure out whether or not the puppet can really predict the future. Includes instructions for making Origami Yoda.